(untitled) (Scientific journal of the Fergana State University, 2023)
Abdulla Aripov’s creative work is very rich. Love, love for the Motherland and the duty of childhood, dedication to the nation, pride in its people, national pride, respect for women, motherhood and love are highly valued. Problems such as nature and spirituality in the interests of people and the Motherland play an important role in poetry.